Interreligious Dialogue through the Media: Perspectives and Limitations of Peace Journalism - Hanitzsch, Thomas (Mediator, 2003)
Uprising clashes and conflicts among Indonesians originated from religious conflicts need an urgent interreligious dialogue. Media, as one of social system agent, is believed could facilitate those kind of dialogue. The concept being introduced here which fitted for such purpose is Peace Journalism. By definition, Peace Journalism is a program or frame of journalistic news coverage, which contributes to the process of making and protecting peace respectively the peaceful settlement of conflicts. The concept of Peace Journalism looks quite suitable especially for Asian and Islamic cultures where the purpose of communication is to generate social harmony and freedom (Hasnain, 1988). However, this concept also has limitations. Those limitations come from the complex relationship between journalism and society, and the challenges from journalism which served well for constructing realities. According to the author, there are five solutions could be achieved in order to maintain a fruitful interreligious dialogue facilitate by Peace Journalism. First, improvement on journalism education and further training for journalist. Second, a thoroughly and in-depth-research by scholars to provide external view on journalism and its operations that may induce self-correction. Third, the growth of “media journalism”. Fourth, a strong press council to control the press. Fifth, and possibly most important, a reliable law system.